2012
DOI: 10.1021/es302206a
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Resolved Measurements of Nighttime Radical Reservoirs in Los Angeles and Their Contribution to the Urban Radical Budget

Abstract: Photolabile nighttime radical reservoirs, such as nitrous acid (HONO) and nitryl chloride (ClNO(2)), contribute to the oxidizing potential of the atmosphere, particularly in early morning. We present the first vertically resolved measurements of ClNO(2), together with vertically resolved measurements of HONO. These measurements were acquired during the California Nexus (CalNex) campaign in the Los Angeles basin in spring 2010. Average profiles of ClNO(2) exhibited no significant dependence on height within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
168
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 146 publications
(184 citation statements)
references
References 49 publications
14
168
1
1
Order By: Relevance
“…Thus, the impact of the daytime HONO (g) source may be greatest near the ground surface and less important aloft. This is consistent with the results of Young et al [2012], which found that radicals generated from nocturnal HONO (g) sources may have greatest impact on oxidation chemistry near the surface during the first half of the sunlit day. This is further indicated by the aircraft measurements of Zhang et al [2009] showing that there is a volume HONO source required to explain observations at higher altitudes (>100 m agl), which cannot be derived from surface production and transport.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the impact of the daytime HONO (g) source may be greatest near the ground surface and less important aloft. This is consistent with the results of Young et al [2012], which found that radicals generated from nocturnal HONO (g) sources may have greatest impact on oxidation chemistry near the surface during the first half of the sunlit day. This is further indicated by the aircraft measurements of Zhang et al [2009] showing that there is a volume HONO source required to explain observations at higher altitudes (>100 m agl), which cannot be derived from surface production and transport.…”
supporting
confidence: 91%
“…In some instances, HONO (g) has been shown to be a comparable OH source to the reaction of O( 1 D) with water vapor (R2) in summer months in Los Angeles [Young et al, 2012], Mexico City [Li et al, 2010a;Volkamer et al, 2010], and Santiago, Chile . Improvements in the accuracy and precision of field instrumentation have generated a consensus that HONO (g) is present throughout the day at mixing ratios on the order of tens to hundreds of parts per trillion by volume (pptv) in many regions, implying a strong source of HONO (g) (up to 2 ppbv h…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundand ship-based BBCEAS field instruments have been used to measure CHOCHO and NO 2 (Washenfelder et al, 2011a;Coburn et al, 2014), HONO and NO 2 (Washenfelder et al, 2011a;Young et al, 2012), NO 3 , and N 2 O 5 (Benton et al, 2010). Kennedy et al (2011) have recently described an aircraft BBCEAS instrument to measure NO 2 , NO 3 , and N 2 O 5 .…”
mentioning
confidence: 99%
“…Scientific questions remain about its sources, sinks, and vertical profile (Zhou et al, 1999;Su et al, 2008;Young et al, 2012;VandenBoer et al, 2013). Existing detection methods can be categorized as wet chemistry, mass spectrometry, and optical spectroscopy.…”
mentioning
confidence: 99%